Outcomes of children with acute myocarditis and dilated cardiomyopathy admitted to a tertiary hospital in the Western Cape south africa: an 8 year study - Carkeek, Katherine (Stellenbosch : Stellenbosch University, 2017)
Thesis (MMed)--Stellenbosch University, 2017.